Impact Evaluation of the Community Engagement Project in the Financial Accounting Training Program for Women Entrepreneurs in the Cayambe Canton - Rodríguez-Salazar, Pedro David (2019)
The projects linked to society aim to generate a positive social impact in the communities, but in many circumstances, this is not analyzed after its application, for this reason the present study analyzes the impact of one of the projects linked to society of the Faculty of Administrative Sciences of the Central University of Ecuador, defining in this way if said project was useful, and if in the case, to propose the possibility of continuing and replicating it. Through the present study, an applicable model for evaluating the social impact of other linked projects is proposed.